Engaging Environments in Tonga Cultivating Beauty and Nurturing Relations in a Changing World - Perminow, Arne Aleksej (Berghahn Books, 2023)
On March 11, 2011, a tsunami warning was issued for Tonga in Polynesia. On the low and small island of Kotu, people were unperturbed in the face of impending catastrophe. The book starts out from the puzzle of peoples' responses and reactions to this warning as well as their attitudes to a gradual rise of sea level and questions why people seemed so unconcerned about this and the accompanying loss of land. The book is an ethnography of the relationship between people and their environment based on fieldwork over three decades.